The influence of caring-based character learning interventions on the practical competencies among nursing students - Permana, Bhakti; Yusuf, Ah; Bakar, Abu; Iswanti, Dwi Indah; Saifudin, I Made Moh. Yanuar (Intelektual Pustaka Media Utama, 2025)
This study aimed to assess the impact of an educational intervention centered on fostering a caring-based character on the practical nursing competency related to ethics, law, and cultural sensitivity. The research employed a quasi-experimental approach with a pre-post design, incorporating a control group. Purposive sampling was used to select 33 respondents for both the intervention and control groups (n=66). The competency measurement instrument was validated and deemed reliable. The intervention, carried out over 12 weeks, utilized a module. Data analysis involved the Wilcoxon match pairs test and Mann-Whitney U-test. The intervention group exhibited a significant improvement in practical nursing competency concerning ethics, law, and cultural sensitivity before and after the caring-based character learning intervention (p<0.001), whereas the control group showed no notable difference (p=0.065). Significant competency differences were observed between the intervention and control groups (p=0.023). The implementation of a caring-based character learning module has the potential to enhance nursing students' competency, particularly in practical aspects related to ethics, law, and cultural sensitivity. It is suggested that nursing education incorporates character learning modules into the curriculum, training programs, or extracurricular activities.